Effect of Morphology on the In Vitro Bioactivity and Biocompatibility of Spray Pyrolyzed Bioactive Glass - Tsion Chuni; Kena Dachasa; Fekadu Gochole; Tadele Hunde; Fetene Fufa Bakare (Advances in Materials Science and Engineering)
Because of its fundamental characteristics, including bioactivity, biodegradability, and nontoxicity, bioactive glasses (BGs) become among the most impressive materials in the area of biomedical applications. It is primarily utilized in the applications of dermal fillers, orthopedic implants, and pharmaceutical delivery systems. Here in this study, simple and continuous methods were employed to produce hollow spherical bioactive glasses (HSBGs) microspheres. Using a spray pyrolysis method, solid and hollow spherical particles were successfully synthesized, and the particle formation mechanism was also discussed in detail. Surface and inner morphologies of synthesized bioactive glass (BG) powders were investigated using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), respectively. BET was employed to measure the pore volume as well as specific surface area for pure BG and BG-derived-PEG powders; all p values are below 0.05, demonstrating noticeable distinction among both forms of synthesized powders. Using energy dispersive spectroscopy (EDS), the constituent components of prepared samples were assessed. In addition, by immersing samples in simulated bodily fluid (SBF) for 12 hr, in vitro bioactivity was tested by SEM. The viability of cells for both BG specimens was evaluated at various extraction concentrations by MTT assay (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenylte-trazolium bromide) for 72 hr. Relying on the Ca/P ratio obtained from SEM-EDS, HSBGs possessed higher hydroxyapatite-forming capacity than solid bioactive glasses (SBGs). In addition, the cell viability of both specimens showed that at all extraction concentrations, they pass the standard biocompatibility levels. Therefore, the HSBGs have better biocompatibility and in vitro bioactivity; hence they are promising for future tissue-engineering development.